From Fossil to Future: The Transformative Role of Renewable Energy in Shaping Economic Landscapes - Nosheen, Misbah; Akbar, Ahsan; Sohail, Mariam; Iqbal, Javed; Hedvicakova, Martina; Ahmad, Sareer; Haider, Syed Arslan; Gul, Azeem (International Journal of Energy Economics and Policy, 2024)
In recent years, numerous countries have embarked on a transformative journey to reshape their energy portfolios by transitioning from fossil-based resources to renewable sources, significantly impacting economic growth. This study aims to scrutinize the influence of renewable energy consumption (REC) on GDP growth responsiveness in the top 20 renewable energy-consuming countries over the period from 1990 to 2021. To ensure robust panel analysis, the study addresses cross-sectional dependence using the diagnostic test proposed by Pesaran (2004). The long-run perspective reveals that both conventional factors of production, encompassing both renewable and non-renewable energy (Fossil Fuel Energy - FEF) consumption, make positive contributions to GDP growth in the sampled countries. Single-country time series analyses further underscore the positive long-run output elasticities concerning renewable energy in the majority of these nations. These findings highlight the pivotal role of renewable energy as a key determinant of sustained GDP growth, indicating that these countries are on a trajectory of sustainable development. The study's implications extend to policy considerations, urging collaborative efforts among governments, international organizations, and energy planners. There is a pressing need for the implementation of strategic renewable energy initiatives across nations. Governments are encouraged to adopt incentive-based policies to optimize the harnessing of renewable energy resources, fostering not only economic growth but also contributing to the global pursuit of sustainable and environmentally conscious practices.